Attraction, femininity and motherhood (Quaderni di Psicologia Clinica, 2022)
In this work, attraction is proposed as a relational event, the most relevant in the relationship between man and woman. Attraction implies, in order to be effective, a verification of reciprocity: attraction – in fact – is a reciprocal event, preluding to the bodies’ approach and implies the acted sexual relationship.The events that follow the failure of attractive reciprocity are analysed, as well as the events resulting from the loss of attraction in the couple relationship.The paths that lead to learn the attractive reciprocity are different for men and women. For the woman, motherhood is an alternative to the relationship of attraction. Sharing third parties is the only effective alternative to the failure of attractive reciprocity.
Keywords: attraction; violence towards women; dependence of women on men; sharing of third things; mind’s unconscious mode of being